ANALISIS MINAT MAHASISWA DALAM MENGGUNAKAN APLIKASI CHATBOT PADA MATA KULIAH AKUNTANSI - Ardiansyah; Hindri Febri Ana Sari (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
In supporting the achievement of learning objectives, the crucial thing that becomes a serious concern is the need for various types of learning media according to the needs of each subject to trigger student interest in independent learning outside the classroom while adapting to today’s technological developments including accounting courses. The purpose of this study was to determine student interest in using chatbot applications in accounting courses. This research method is descriptive quantitative. The data used in this study are primary and secondary data. Based on the findings in this study, it is known that students’ interest in using chatbot applications is in the very high category with a total score of 329 points or 87%. This finding indicates that chatbots can be one of the learning media in accounting courses because they are able to encourage students’ interest in learning outside the classroom. Nevertheless, the efforts of lecturers in maximizing learning in the classroom remain the main thing in the teaching and learning process. In general, the obstacles faced in using chatbots for students are that each student’s internet signal and quota are different. In general, students’ interest in using chatbots is due to the chatbot working system that allows students to ask robots that have available features/buttons/menus and chatbot designs that do support Android users. The theoretical contribution of the results of this study is that students’ interest in using chatbot applications in accounting courses is very high, this gives confidence in the implementation of chatbot applications. The practical contribution is as a material for consideration in updating the RPS (Semester Learning Plan), practicum modules, and job sheets for Accounting courses.